Functional food candidate from Indonesian green algae Caulerpa racemosa (Försskal) J. Agardh by two extraction methods: metabolite profile, antioxidant activity, and cytotoxic properties - Taslim, Nurpudji Astuti; Hardinsyah, Hardinsyah; Radu, Son; Mayulu, Nelly; Tsopmo, Apollinaire; Kurniawan, Rudy; Tallei, Trina Ekawati; Herlina, Tati; Maksum, Iman Permana; Nurkolis, Fahrul (Elsevier, 2024)
There is an urgent need to explore natural sources like Caulerpa racemosa (Försskal) J. Agardh for bioactive compounds with strong antioxidant and therapeutic potential, providing sustainable alternatives for health and pharmaceutical innovation. This study aimed to determine the phytochemical profile and biological activities of extracts from edible green algae–known as sea grapes (C. racemosa). This present study has successfully identified secondary metabolites through untargeted metabolomic profiling by liquid chromatography-high resolution mass spectrometry (LC-HRMS) as well as a bioactive peptide. The antioxidant activity and cytotoxicity of extracts from C. racemosa and compounds were determined. A total of 103 metabolites were identified in the C. racemosa extract obtained by the maceration (ME), while 48 metabolites were detected in the soxhlet extract (SE). The sequence of the identified peptide was ELWKTF (Glu-Leu-Trp-Lys-Thr-Phe; C41H58N8O) and its abundance was identified in the α-chymotrypsin hydrolysate of C. racemosa. In the antioxidant activity test, SE and purified fraction 1 (PF1) had EC50<EC50 of control or Glutathione (GSH) in terms of 2,2-Diphenyl-1-picrylhydrazyl (DPPH) inhibition, and PF1 had EC50<EC50 of control or Trolox in terms of 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) inhibition. In general, C. racemosa contains antioxidant nutrients, metabolites, and bioactive peptides, suggesting its promising potential as a functional food and pharmaceutical.